Awareness and practice of birth preparedness and complication readiness among pregnant women in the Bamenda Health District, Cameroon - Yunga Patience Ijang; Samuel Nambile Nambile Cumber; Claude Ngwayu Nkfusai; Mbinkar Adeline Venyuy; Fala Bede; Pierre Marie Tebeu (BMC, 2019)
Abstract Background Birth preparedness and complication readiness has as goal to reduce maternal and neonatal mortality. This concept developed by the organizations of the United Nations permits pregnant women and their families seek health care without delay in case of obstetric complications and delivery. Though its benefits have been proven in several countries, little is known of this in Cameroon and specifically in the North West Region. Therefore, the intention of the study was to assess the awareness and practice of birth preparedness and complication readiness in this health district. Methods This was a facility-based cross sectional study carried out in the Bamenda health district of the North West Region, Cameroon. Three hundred forty-five pregnant women of ≥32 weeks gestational age seen at the antenatal consultation units were recruited. The dependent variable was birth preparedness and complication readiness while the independent variables were the socio-demographic and reproductive health characteristics. Data collected was analyzed with SPSS and Microsoft excel. Frequency distributions were used to determine the awareness and practice of birth preparedness and complication readiness. Results Of the 345 pregnant women included in this study, 159(46.1%) were aware of birth preparedness and complication readiness. The practice of birth preparedness and complication readiness was unsatisfactory as only 65(18.8%) were considered prepared. Conclusion Education and counselling on birth preparedness and complication readiness is not made available to the pregnant women resulting in poor knowledge. Thus, reflected in the low practice of preparation for birth and its complication observed.